Diseño de un Sistema de Gestión de Inventarios para el establecimiento comercial “Mercadito Santa Marta” en La ciudad de Santa Marta (2023)
The present investigation consists of designing an inventory management system for the commercial establishment "Mercadito Santa Marta", since currently there are no has an inventory management system that helps you know what products are available in stock, how to locate them more easily and avoid the loss of the products, leading to the loss of customers due to poor service and losses in the bandages. That is why it is very important to have an adequate management system of inventories that help the company to have a reliable and secure record of what has by offering a better product and service. For this reason, the specific objectives of this project are to find the tools to carry out a diagnosis of the products of the demand as of the suppliers, then develop a classification where the products that are most important and relevant to the establishment in order to determine what the better inventory management system that adjusts to the needs of the products.